Emergence of Unusual Microorganisms in Microflora of Pilonidal Sinuses: A Multiple Case Series. Issue 1 (January 2023) - Banerjee, Tuhina; Singh, Aradhana; , Anurag; Pal, Sourav; Basu, Somprakas
Abstract : PURPOSE: Recent reports have noted an emergence of unusual organisms in microflora of pilonidal sinus (PNS); this study was undertaken to identify the primary microbial flora associated with infected primary PNS over a period of 1 year. DESIGN: A prospective multiple case series. SUBJECTS AND SETTING: A case series of 20 patients with primary PNS in a tertiary care center in Varanasi, India, was studied. The study was conducted at the Department of Microbiology and General Surgery, Institute of Medical Sciences, Varanasi, over a period of 1 year (September 2016 to July 2017). METHODS: Purulent exudate (pus) samples were collected from 20 patients with primary PNS from the discharging sinuses by aseptic methods. Samples were assessed for aerobic and anaerobic flora by conventional culture and molecular methods. Antimicrobial susceptibility testing was done for bacterial isolates. Bacterial diversity was compared with the demographic and clinical profile of the sinuses by multiple correspondence analysis. RESULTS: Of the total cases, 11 (55%) had purulent discharge, among which all showed polymicrobial flora. The ratio of aerobic to anaerobic organisms was 1:2 (16/32). Escherichia coli ( E. coli, 4, 36.36%) and Enterococcus faecalis ( E. faecalis, 4, 36.36%) were commonly isolated. Bifidobacterium was the most frequent anaerobe. Detailed molecular analysis revealed the presence of Kocuria flava as an unusual pathogen. On statistical analysis, factors like male gender, increased body mass index, absence of hair in sinus, presence of features of hirsutism, and absence of Fusobacteria were closely associated with one another in these PNS cases. CONCLUSIONS: The case series revealed the predominance of anaerobes in primarily infected PNS cases. Bifidobacterium spp and unusual pathogens like K. flava were among the emerging pathogens in infected PNS. Use of better molecular diagnostic facilities in addition to the conventional methods might enhance the verified diversity of microorganisms in such cases.